Financial literacy and poverty reduction: The case of Indonesia - Media Wahyudi Askar; Bazoumana Ouattara; Yin-Fang Zhang (Asian Development Bank Institute (ADBI), 2020)
Given its role in affecting financial behavior, financial literacy has received considerable attention from researchers and policy makers alike. This paper employs data from a nationally representative survey in Indonesia to investigate the impact of financial literacy on poverty, which is a downstream welfare indicator. Consequently, we have constructed a composite financial literacy index. Our results reveal that financial literacy plays an important role in reducing poverty. This finding is robust, irrespective of the measure of financial literacy and regardless of the instrumentalization strategy adopted.
Keywords: G530; I320; 330; financial literacy; poverty; developing countries